Development of a GIS-based CCTV Information System to monitor traffic conditions in Rembang - Farid Maulana Ishaq; Fajar Sodiq; Syakur (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
The development of information technology, particularly Geographic Information Systems (GIS), can be utilized for data analysis and productivity enhancement, including in traffic condition monitoring. The existing system in Rembang only displays CCTV video streams in a static manner without real-time status integration. Therefore, this study aims to develop a GIS-based CCTV information system integrated with online/offline status, community participation, and open web-based access to support traffic monitoring needs in Rembang. The software development method used is Extreme Programming (XP), which focuses on rapid adaptation to changing user requirements. The system is designed to display camera locations interactively on a digital map, integrate real-time CCTV data (online/offline status), and provide live video streaming access through the YouTube API within a single web-based platform. The results of Black Box Testing indicate that all system functions including admin login, CCTV data management (CRUD), community reporting features, and video streaming playback on the map operate correctly, with all test scenarios validated. In conclusion, this research successfully delivers a solution that supports traffic monitoring and security in Rembang by providing open access for general users and effective data management capabilities for administrators.